2022
DOI: 10.3390/sym14010129
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Mitigation of Curved Continuous Girder Bridge Considering Collision Effect

Abstract: Due to structural irregularity, curved bridgesaremore likely to cause non-uniform collisions and unseating between adjacent components when subjected to earthquakes. Based on the analysis of the collision response of curved bridges duringearthquakes, and according to the seismic characteristics of curved bridges, research was carried out on pounding mitigation and unseating prevention measures. A curved bridge with double column piers was taken as an engineering example, and a finite element model of curved br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…By combining Equation (1) with Equation ( 2), the roll angle of the vehicle body can be determined as shown in Equation (3).…”
Section: Without Considering E-b Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining Equation (1) with Equation ( 2), the roll angle of the vehicle body can be determined as shown in Equation (3).…”
Section: Without Considering E-b Parametersmentioning
confidence: 99%
“…In this case, centrifugal forces result from the outward centrifugal acceleration of vehicles, which have potential effects on the stability and structure of the bridge. Therefore, the centrifugal forces of vehicles become critical factors in bridge design, including the design of static and dynamic bearing capacities [3,4]. Conceivably, the introduction of the centrifugal force makes the problem of the vehicle-induced dynamic response of curved girder bridges more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al's [4] study on the curved unsymmetrical bridge model with non-uniform contact collision between adjacent components for seismic mitigation and unseating prevention, the damping devices and the pounding mitigation device can be used as a combinatorial seismic mitigation system to form three kinds of combined seismic mitigation cases. The results indicated that it is effective at reducing the response to a pounding force, stress, damage, girder torsion and displacement, and achieved the goals of seismic mitigation and unseating prevention.…”
Section: Introductionmentioning
confidence: 99%